Income-driven behavioral heterogeneity in rural energy transition: a TPB analysis of China’s coal-to-electricity policy - Yang, Mingjie; Zhang, Xiaodong; Guo, Rui; Li, Yaolong; Zhong, Fanglei (Frontiers in Energy Research, 2025)
To address air pollution and advance clean energy adoption, China’s “coal-to-electricity“ policy has encountered varied compliance among farmers due to income disparities. Integrating the Theory of Planned Behavior with income stratification, this study examines rural households’ behavioral intentions in Pu County, Shanxi, using structural equation modeling on survey data from 221 households. Results show distinct drivers across income groups: low-income farmers rely heavily on perceived behavioral control (β = 0.396, p < 0.01), emphasizing financial constraints; middle-income farmers balance policy trust and environmental awareness; and high-income farmers respond strongly to subjective norms (β = 0.760, p < 0.01), reflecting social influence. These findings argue against a uniform subsidy approach and propose tailored strategies—direct financial support for low-income groups, technical incentives for middle-income farmers, and normative interventions for high-income adopters—offering behaviorally-informed policy insights for advancing SDG 7 and SDG 13 in developing countries.